Real-time mobile application development - Seah, Jia Da. (2009)
With the advancement of technologies, the demand for Real-Time applications has increased considerably in recent times. This demand has led to the increased use of the widely available Java programming language as well as open source operating systems such as Linux. This project aims to describe and illustrate the differences between non Real-Time and Real-Time applications, as well as to implement Real-Time theories by designing a Real-Time application. The topic of interest for the application design would be an application that could monitor public transport waiting times. Public transportation plays an increasingly important role in building sustainable cities. However, a major deterrent to using public transport is the uncertainty of the length of waiting times at stops. Thus, the success of this project would bring about great benefits to the general public transport commuters. The embedded application would be designed using Sun Java wireless toolkit based on Microsoft XP Operating system, which would then be tested on mobile platforms with Windows Mobile version 6.0 operating systems.